Thailand's 2023 Election: A Liberal Moment in a Competitive Authoritarian System - Aim Sinpeng; Greg Raymond (Journal of Current Southeast Asian Affairs)
This article introduces a Special Issue on Thailand's 2023 election. The articles unravel the factors driving the surprising results of the 14 May poll, which prima facie delivered impressively liberal outcomes, only later to be confounded by a series of conservative moves. Drawing on rich empirical data from fieldwork, interviews, and surveys, the articles uncover important societal and political changes that produced the election results, especially new social cleavages along generational lines, new styles of campaigning, and the relative decline of populist money politics. The papers test new concepts and add to a range of literatures including gender in politics, digital politics, diaspora politics, and authoritarian securitisation.